Généalogie et transmission du nom en Béarn du XVIIIe au XXe siècle - Roseline Segrestin; Lucienne Jakobi; Pierre Darlu (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
From parish records and public registries, the genealogies of people born between 1744 and 1975 at Arthèzd’Asson, Béarn (France), have already been reconstructed from previous studies. The surnames given to each member of these genealogies were recorded several times in a lifetime (birth, marriage, children’s births, death). The files include 12,000 births, 1500 unions, 4000 siblings. The modes of transmission of surnames through the genealogies were also described. Results show that surnames, as transcribed in the records, often changed during a lifetime and were transmitted through the female line to a large extent. Consequently, the traceability of surnames through the genealogies is uncertain. Some mating strategies were also detected. The mode of designation of people in this Béarnaise society is discussed, as well as the uncertainties of inferences based on surnames when the rules of surname transmission are not regularly applied.